DEVELOPMENT OF BUILDING INFORMATION MODELS OF THE PROCESS OF REMOTE SURVEYING OF EMERGENCY BUILDINGS USING UAVS - Gorda, O. V.; Chervyakov, Yu. M.; Hryhorovskyi, A. P. (Science and Transport Progress, 2022)
Purpose. The adoption of organizational and technological solutions for the elimination of the consequences of accidental destruction of buildings due to overtime effects due to military actions is based on the prompt receipt of information about the technical condition of the object, since the performance of priority emergency and rescue work immediately after a disaster or accident, when there is a threat to human life, requires the rapid adoption of such decisions in conditions of uncertainty regarding the prevention of secondary destruction. It is possible to minimize the duration of the decision-making process under conditions of uncertainty by optimizing the technology of obtaining information, that is, the survey process using automated remotely controlled aircraft in combination with building information modeling of the process of obtaining and processing information about the technical condition of the object. Methodology. Analysis and consideration of factors affecting the bearing capacity and organizational and technological features of the process of loss of strength of concrete and reinforced concrete building elements in case of detonation of an open charge on their surface, depending on the growth and fusion of microcracks under the influence of applied stresses for the compilation of an information model of dynamic destruction. The results. Based on the results of the analysis of the process of remote inspection of buildings damaged as a result of military operations using unmanned aerial vehicles, the authors developed a method of building information modeling of partial destruction of large-panel buildings due to extra-design influences. The stages of construction of the information model of the object are given. Findings. Based on the results of the analysis of the process of remote inspection of buildings damaged as a result of military operations using unmanned aerial vehicles, the authors developed a method of building information modeling of partial destruction of large-panel buildings due to extra-design influences. The stages of construction of the information model of the object are given. Originality. For the first time, a method of building information modeling of partial destruction of large-panel buildings due to extra-project influences has been developed to optimize organizational and technological solutions for strengthening structures in the centers of such destruction for the possibility of emergency rescue operations. Practical value. It consists in minimizing the duration of the decision-making process in conditions of uncertainty and the risk of ineffective decision-making in conditions of insufficient information about the object damaged as a result of extra-project impact of man-made nature.